DESAIN DIDAKTIS TERHADAP MATERI BILANGAN BERPANGKAT SMA BERDASARKAN LEARNING OBSTACLE (ONTOGENI OBSTACLE) - Sri Wahyuni; Anggita Maharani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research is a Didactic Design Research (DDR) using qualitative methods. The subject of this study was 1 (one) student of grade X-2 SMA Negeri % Cirebon. The purpose of this study is to 1) know the didactic design to overcome the existing Ontogenic obstacles related to the Rank Number material, 2) find out the students' response in implementing didactic designs related to the power number material. The results of this study suggest that: 1) the didactic design made by the researcher consists of; Hypothetical didactic design 1 (contains materials, examples, and practice questions about power numbers), hypothetical didactic design 2 (contains materials, examples and practice questions about power numbers). 2) Students respond well to the implementation of didactic design, empirical didactic design is a combination of material and analysis of hypothetical didactic designs 1 and 2 that are successfully implemented well